INVESTIGATING THE DETERMINANTS OF GREEN SUPPLY CHAIN MANAGEMENT VALUE CREATION FOR DESIGN SERVICE SUCCESS (The Case of Taiwan High-tech Industry) - Dwiyanti, Dessy; Lin, Yichen (UG Journal, 2014)
Future competition advantage will be about business partnership team in termsofdesign service industry to obtain sufficient resources and knowledge. To do so,a good supply chain management is inevitable, and by incorporating the greenissue into new product development. The green design has increasingly consideredas systematic methodfor companies to reduce the environmental impact of theirproducts and processes while simultaneously cutting costs and increasing productmarketability. The present research proposes conceptualframework related togreen supply chain management value creation to improve design serviceperformance through several critical condition factors and critical abilityfactors.This research has adequate sample size for Structural Equation Model analysisthrough AMOS software. The results successfully construct business processsynchronization and supply-demand element realignment as a critical conditionfactors in the context of green SCM area and several ability factors as a criticalability dimension. This paper also approved the hypothesis that green supply chainmanagement value creation has positively influence design service performance.The results also cont ributes several new insight for academic as well as practicalimplication.